A discrete limit theorem on the complex plane for one class of general Dirichlet series - Macaitienė, Renata (Lietuvos matematikos rinkinys, 2005)
In the paper a discrete limit theorem in the sense of weak convergence on the complex plane for general Dirichlet series with improved condition is presented.
Keywords: general Dirichlet series; probability measure; random variable; weak convergence